The origin of the KLT relations and nonlinear relations for Yang-Mills amplitudes - Barreiro, Luiz Antonio [UNESP]; Medina, Ricardo (Elsevier, 2020)
By means of a kinematic analysis of tree level graviton amplitudes we find, at least through six points, that the reason of their decomposition as a sum over products of gauge boson amplitudes is on-shell gauge invariance and unitarity. As a by-product of our analysis we find nonlinear relations obeyed by Yang-Mills amplitudes. All our results are valid for arbitrary spacetime dimensions.
Keywords: Gluon amplitudes; Graviton amplitudes; KLT relations